Mental health and physical activity indicators of banking sector workers during the COVID-19 pandemic - Oliveira, Íris Silveira (2023)
Introduction: Physically active individuals seem to have better indicators of mental health and stress compared to their insufficient physical activity peers. However, the analysis of physical activity levels and mental health indicators of bank employees has not been explored during the COVID-19 pandemic. Objective: To analyze depression, anxiety, stress, and physical activity scores in bank employees during the COVID-19 pandemic. Method: An associative comparative strategy was applied with 21 bank employees (24-44 years, 71.4% women) in a city in Northeast Brazil. An online questionnaire was applied exploring sociodemographic and anthropometric information, indicators of anxiety, depression, and stress (EADS-21), occupational function, and physical activity levels. The correlation between the EADS-21 scores and the physical activity levels was obtained using Spearman's Rho coefficient and the comparison of indicators between insufficiently active and physically active workers was performed using the Mann-Whitney U test. Results: The physical activity levels showed a weak and inverse correlation with anxiety (Rho= −0.15), depression (Rho= −0.35), and stress (Rho= −0.11) scores. In addition, it was found that there was no statistically significant difference between insufficiently active vs. physically active bank employees concerning anxiety (P= 0.719), depression (P= 0.548), or stress (P= 0.842). Conclusion: Mental health and stress indicators were inversely associated with regular physical activity levels. In addition, scores of anxiety, depression, and stress were similar between physically active and insufficiently active bank employees.